Results of total colonoscopy in the diagnosis of polyps. Case studies in Villavicencio, Colombia (2017)
Introduction: Any elevation above the normal plane of the colonic mucosa is considered a polypoid projection. As age increases, polyps are more likely to be found; in addition, polyps larger than 1 cm of diameter may potentially lead to a malignant neoplasm. Objective: To establish the frequency, size, location and age groups of colonic polyp lesions in patients who underwent colonoscopy at Hospital Departamental in Villavicencio during 2009-2014. Materials and methods: The results of 411 diagnostic colonoscopies were analyzed. Data collection and statistical description was done using SPPSS 2011 software. Results: 43 (11%) polyps were smaller than 1cm; 16 (4%) were between 1cm and 2cm long; no polyps larger than 2cm were found, and the remaining results did not show any abnormality. Polyps were found in all segments of the colon in the 41-50 age group, but the highest percentage (11%) was observed in the 71-80 age group. 68.7% of polyps larger than 1cm and 67% smaller than 1cm were found in the left colon. Conclusion: In population groups under 40 years of age, the incidence of polyps is low in the left colon and very low in the right colon.